The practice of gold investment among women entrepreneurship at Siti Khadijah Market (Kelantan) / Anis Syazwani Mohd - Mohd, Anis Syazwani (Academy of Contemporary Islamic Studies, 2018)
The objective of the research is to know the practice of gold investment among women entrepreneurship at Siti Khadijah Market (PSK), Kota Bharu, Kelantan. The researcher found that the majority of the traders are women, the researcher eager to study in detail. Gold investment is one of great investment because of the advantage of the gold itself. In Malaysia, there is two type of gold investment practices which is physical gold investment and gold investment account. In practicing the gold investment, the people also must consider the Shariah condition on practicing the gold investment. In this research, the researcher hopes that the study can help the people in understanding more about the gold investment that can be practice at Malaysia especially at the Kelantan.